Implementasi Asas Ne Bis In Idem dalam Putusan Hakim yang Berkekuatan Hukum Tetap pada Perkara Pidana - Andrew, Andrew; Rahaditya, R. (UNES Law Review, 2023)
This study aims to determine the application of the ne bis in idem principle in judge decisions that have permanent legal force in criminal cases. The research method used is a normative juridical approach with qualitative methods. The results of the study stated that the principle of nebis in idem in criminal cases aims to provide protection for the accused so that he does not get a decision for the same case repeatedly. It also aims to maintain respect for the human rights of perpetrators. This principle cannot be applied to decisions 1) Decisions declaring the indictment null and void. 2) Decision declaring the Claims Unacceptable. 3) Decision declaring the Court Not Competent. This principle can be applied if the criminal case has the following elements: 1) it has the same legal basis and reasons as the case that has been decided. 2) the parties involved in the case are the same party. Nevertheless, to implement and guarantee justice for every citizen. The state provides leeway for everyone to conduct a review. This is because judges are human beings who sometimes make mistakes.